The East Greenland Coastal Current : its structure, variability, and large-scale impact - Sutherland, David A. (David Alan) (Massachusetts Institute of Technology, 2008)
Thesis (Ph. D.)--Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2008. Includes bibliographical references (p. 155-161). The subtidal circulation of the southeast Greenland shelf is described using a set of high resolution hydrographic and velocity transects occupied in summer 2004. The main feature present is the East Greenland Coastal Current (EGCC), a low-salinity, high velocity jet with a wedge-shaped hydrographic structure characteristic of other surface buoyancy-driven currents. The EGCC was observed along the entire Greenland shelf south of Denmark Strait, while the transect north of the strait showed only a weak shelf flow. This observation, combined with evidence from chemical tracer measurements that imply the EGCC contains a significant Pacific Water signal, suggests that the EGCC is an inner branch of the polar-origin East Greenland Current (EGC). A set of idealized laboratory experiments on the interaction of a buoyant current with a submarine canyon also supported this hypothesis, showing that for the observed range of oceanic parameters, a buoyant current such as the EGC could exhibit both flow across the canyon mouth or into the canyon itself, setting the stage for EGCC formation. Repeat sections occupied at Cape Farewell between 1997 and 2004 show that the along shelf wind stress can also have a strong influence on the structure and strength of the EGCC and EGC on timescales of 2-3 days. Accounting for the wind-induced effects, the volume transport of the combined EGC/EGCC system is found to be roughly constant (-2 Sv) over the study domain, from 68*N to Cape Farewell near 60°N. The corresponding freshwater transport increases by roughly 60% over this distance (59 to 96 mSv, referenced to a salinity of 34.8). This trend is explained by constructing a simple freshwater budget of the EGCC/EGC system that accounts for melt water runoff, ...